Victorian reformation : the fight over idolatry in the Church of England, 1840-1860 - Janes, Dominic (Religion, culture, and history series., 2009)
In early Victorian England, the cross was widely thought to be a deadly idol that led worshippers to the devil. Victorian Reformation is a study of the intense anxieties surrounding 'idolatry' which was, in a narrow sense, the worship of idols, but also devotion to anything that intervened between the believer and God. In early Victorian England there was intense interest in understanding the early Church as an inspiration for contemporary sanctity. One aspect of this was a surge in archaeological inquiry and the construction of new churches using medieval models. A number of Anglicans began t.